A participatory approach to tracking system transformation in clusters and innovation ecosystems—Evolving practice in Sweden's Vinnväxt programme. Issue 2 (18th April 2022) - Wise, Emily; Eklund, Moa; Smith, Madeline; Wilson, James
Abstract: For decades, cluster initiatives and funding programmes have been used as instruments of industrial and innovation policy—addressing system failures by strengthening linkages among actors, fostering innovation, and developing more effective innovation systems. More recently, a growing segment of these initiatives are also focused on driving system-level transformation and contributing to broader societal benefits. This segment is characterized by larger-scale and longer-term strategic efforts involving a variety of stakeholders across different parts of society, aimed at contributing to addressing societal challenges. These characteristics are shared with the emerging frame of transformative innovation policy, which highlights the importance of embedded practices of learning and reflexivity to enable continuous monitoring of progress and inform and adapt the direction of systemic change processes—requiring new approaches to governance and evaluation. Despite deep experience with implementing cluster programmes and other systemic innovation policy instruments, practitioners still struggle with monitoring and evaluation. Current approaches focus on evidencing strengthened innovation (and economic effects) on the level of firms and research actors, and fail to capture contributions on the level of the broader system. This article presents an evolving approach for tracking system transformation in clusters and collaborative innovation initiatives. Through an interactive, co-development process with initiatives in the Swedish Vinnväxt programme, this research proposes a definition and set of system effect categories for cluster initiatives. It tests a participatory approach for tracking their contribution to system-level change over time, providing an initial case on which to build and apply in other transformative innovation programmes.